A secret kept - Rosnay, Tatiana de, 1961- (New York : St. Martin's Press, 2010)
It's been thirty years since Antoine's and Melanie's mother died. But when a visit to the sea at Noirmoutier Island triggers painful memories of their haunting childhood--and Melanie lies in the hospital recovering from a near fatal accident--Antoine must confront his past and also his troubled relationships with his own children.
Keywords: Brothers and sisters -- Fiction; Family secrets -- Fiction; Noirmoutier Island (France) -- Fiction; Psychological fiction